Checklist of Croatian amphibians and reptiles with bibliography of 250 years of research - Dušan Jelić (Natura Sloveniae)
An updated checklist is presented for the amphibian and reptile fauna of Croatia. According to historical and recent literature sources, 20 amphibian and 41 reptile species have been recorded so far. Two reptile species, Blanus strauchi and Typhlops vermicularis, are considered doubtful, although there are individual museum vouchers for the country. Presence of a total of 59 species can be considered valid, with two additional considered doubtful. This paper summarizes data from 700 scientific and popular publications, which is the first attempt to publish a complete Croatian herpetological bibliography. Full bibliography is also given for all occurring species and constitutes a basis for future publications.